기업의 환경성과가 기업가치에 미치는 영향 - 전정주(Chun, Chung-Joo) (대한경영학회지, 2012)
본 연구는 기업의 환경성과가 해당기업의 가치에 미치는 영향에 대해서 한국기업을 대상으로 실증분석을 실시하기로 한다. 환경성과에 대한 투자는 기업가치와 상충되는 것으로 알려져 왔다. 즉 환경성과에의 투자자체는 명시적인 효익이 확보되기 힘들기 때문에 기업들은 이익극대화를 위해서라면 오히려 환경에의 투자를 감소시켜야 한다는 주장도 제기되고 있다. 한국의 경우, 환경성과에의 투자가 아직 미미한 상황이고 특히 환경규제와 관련하여 아직 선진국보다 미비한 부분이 있기 때문에 환경성과가 기업가치에 미칠 수 있는 영향에 대한 문제에 대해서는 실증분석이 필요한 상황이다. 본 연구는 한국의 경제정의실천시민연합에서 발표하고 있는 환경보호와 관련된 점수를 바탕으로 5년 동안 꾸준히 환경성과에 투자를 실시한 기업을 대상으로 환경성과가 해당기업의 가치에 미칠 수 있는 영향에 대해서 실증분석을 실시하였다. 실증분석 결과 환경성과에 대한 장기투자는 기업가치에 오히려 부정적인 영향을 미치는 것으로 나타났다. 본 연구는 2000년 이후의 최근의 자료를 대상으로 환경성과가 기업가치에 미칠 수 있는 영향에 대해서 실증분석을 실시하였다는 점에서 공헌점이 있을 것으로 판단된다. This paper examines the relevancy between the environmental performance and the firm value of Korean companies in the manufacturing industry. Many prior papers suggest that environmental performance support the firm value. On the other hand, some papers suggest that investment in environmental performance does not guarantee higher economic benefit and thus that it can be more beneficial for a company to maintain minimum level of environmental investment. Korea environmental laws and regulations are rather loose compared to other more developed countries in the U.S. or Europe. As such, it is necessary to consider more rigorous empirical analyses rather than to directly compare Korean companies to that of the developed countries. Using five years data of succeeding environmental performance, this paper examines that environmental performance is negatively associated with the firm value. This is consistent with prior literatures which suggest that environmental performance do not guarantee higher economic benefit. This paper has some contribution in a sense that the government or its regulators can consider making higher direct tax benefit or grant subsidiaries to Korean companies which choose to remain active in its investment related to environmental performance. KCI Citation Count: 12